Why West Acehnese Shift Their Dialect to Other Acehnese Dialect - Nur Aini; Zulfadli A. Aziz; Bukhari Daud (English Education Journal, 2018)
The aim of this study was to investigate the reasons for dialect shifting by speakers from West Aceh when they speak Acehnese outside of the West Aceh area. A qualitative method was used for this research. The data was collected using interviews following an interview guide. The researcher interviewed the informants who were all from West Aceh and living in Banda Aceh for educational purposes. Based on the results from the interviews, the researcher found that the West Acehnese shifted their dialect into other dialects when they spoke with other Acehnese outside of West Aceh. The dialect was shifted by them for various reasons, such as lacking confidence to use their own dialect, to avoid embarrassment or being ridiculed by other speakers, to make them easier to be understood, to get acceptance and respect from the community where they were and due to being influenced, unconsciously, by other, more dominant dialects.